Silicon negative electrode material, and secondary battery and electric equipment comprising same

By introducing porous structures and fast ion conductors into the silicon anode material of sulfide-type all-solid state batteries, and doping them with Group IIIA, Group VIA and Lanthanide elements, the problem of transmission rate and volume changes of the silicon anode material in solid-state batteries is solved, and the battery's magnification and cycling performance are significantly improved.

CN119581526AActive Publication Date: 2025-03-07SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411750464.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

When using silicon negative electrode materials, existing sulfide type all-solid state batteries have problems such as slow ion/electron transfer rates, drastic volume changes, and interface contact failure after cycling, resulting in poor rate performance and cycling performance.

Method used

A silicon negative electrode material is used, which includes silicon-based particles having a porous structure and a fast ion conductor. Group IIIA elements, Group VIA elements and lanthanide elements are introduced into the silicon-based particles, and the fast ion conductor is filled in the porous structure.

Benefits of technology

Through the above design, the transmission rate of lithium ions/electrons inside the negative electrode sheet is improved, the volume expansion of the silicon negative electrode is alleviated, and the magnification and cycling performance of the secondary battery are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581526A_ABST
    Figure CN119581526A_ABST
Patent Text Reader

Abstract

The invention relates to the field of secondary batteries, and discloses a silicon negative electrode material, a secondary battery containing the silicon negative electrode material, and electric equipment. The silicon negative electrode material comprises silicon-based particles and a fast ion conductor, the silicon-based particles have a porous structure, and the fast ion conductor is filled in a pore channel of the porous structure; the silicon-based particles comprise a silicon element and doping elements, and the doping elements comprise at least two of IIIA group elements, VIA group elements and lanthanide elements. The doping elements are introduced into the silicon-based particles, and the transmission rate of lithium ions / electrons in the negative plate can be improved and the volume expansion of the silicon negative electrode can be relieved by utilizing different functions of different doping elements and through high-entropy design; and meanwhile, the silicon-based particles also have a porous structure, and the fast ion conductor is filled in a pore channel, so that the conduction rate of lithium ions in the negative electrode can be further improved, and the volume expansion can be further relieved to ensure that the multiplying power and the cycle performance of the secondary battery are good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a silicon negative electrode material and a secondary battery and electrical equipment containing the same. Background Art

[0002] Traditional lithium-ion secondary batteries use liquid electrolytes to ensure efficient and stable operation of the battery. However, liquid electrolytes are flammable and can easily cause fire or explosion when subjected to mechanical or thermal stress. All-solid-state batteries constructed by replacing the flammable liquid electrolytes in traditional lithium-ion batteries with non-flammable, non-volatile, and non-leaking solid electrolytes can fundamentally improve battery safety.

[0003] At present, the types of solid electrolytes mainly include oxides, sulfides, halides, polymers, etc. Among them, sulfide solid electrolytes have the highest room temperature ionic conductivity and are considered to be the most promising solid-state battery system. On this basis, researchers have tried to use positive / negative electrode active materials with large specific capacity to improve the energy density of all-solid-state batteries, such as using high-nickel lithium-rich materials for positive electrode active materials and silicon negative electrodes for negative electrode active materials, so that all-solid-state batteries can achieve high energy density and high safety at the same time. However, when silicon negative electrodes are applied to sulfide-type all-solid-state batteries, there are problems such as slow ion / electron transfer rate, drastic volume changes, and interface contact failure after cycling, resulting in poor rate performance and cycle performance of the battery. Summary of the invention

[0004] In view of this, the present application provides a silicon negative electrode material to solve the problem of poor rate and cycle performance of existing sulfide-type all-solid-state batteries.

[0005] According to an embodiment of the present application, in a first aspect, a silicon negative electrode material is provided, wherein the silicon negative electrode material comprises silicon-based particles and a fast ion conductor, wherein the silicon-based particles have a porous structure, and the fast ion conductor is filled in pores of the porous structure;

[0006] The silicon-based particles include silicon element and a doping element, wherein the doping element includes at least two of Group IIIA elements, Group VIA elements, and lanthanide elements.

[0007] In some optional embodiments, the silicon negative electrode material further includes at least one of the following features:

[0008] a. The Group IIIA element includes at least one of B and In;

[0009] b. The VIA group element includes at least one of S and Se;

[0010] c. The lanthanide element includes at least one of La and Ce.

[0011] In some optional embodiments, the silicon negative electrode material further includes at least one of the following features:

[0012] d. The molar ratio of the Group IIIA element in the silicon negative electrode material is 0.1-0.2;

[0013] e. The molar ratio of the VIA group element in the silicon negative electrode material is 0.1-0.2;

[0014] f. The molar ratio of the lanthanide element in the silicon negative electrode material is 0.05-0.1.

[0015] In some optional embodiments, the porosity of the silicon negative electrode material is 1%-15%.

[0016] In some optional embodiments, the median particle size of the silicon negative electrode material is 0.8 μm-5 μm.

[0017] In some optional embodiments, the silicon negative electrode material further includes at least one of the following features:

[0018] g. Based on the mass of the silicon negative electrode material, the content of the fast ion conductor is 5%-10%;

[0019] h. The elastic modulus of the fast ion conductor is 2MPa-200MPa;

[0020] i. The fast ion conductor comprises at least one of a sulfide electrolyte, a polymer electrolyte, and an oxygen-containing inorganic electrolyte.

[0021] In some optional embodiments, the fast ion conductor is a polymer electrolyte and an oxygen-containing inorganic electrolyte, and the content of the oxygen-containing inorganic electrolyte is 10%-20% based on the mass of the fast ion conductor.

[0022] In some optional embodiments, the sulfide electrolyte includes Li 10 GeP2S 12 、Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 , at least one of Li3PS4;

[0023] The polymer electrolyte includes at least one of polyethylene oxide (PEO), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polymethyl methacrylate (PMMA), and polyacrylonitrile (PAN);

[0024] The oxygen-containing inorganic electrolyte includes Li7La3Zr2O12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1.3 Al 0.3 Ge 1.7 (PO4)3、Li 0.33 La 0.55 At least one of TiO3.

[0025] According to an embodiment of the present application, in a second aspect, a secondary battery is provided, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte, wherein the negative electrode sheet comprises a negative electrode collector and a negative electrode active layer arranged on at least one side surface of the negative electrode collector, and the negative electrode active layer comprises the silicon negative electrode material described in the first aspect of the present application.

[0026] In some optional embodiments, the negative electrode sheet has a sheet resistance of 0.5 mΩ-1 mΩ.

[0027] In some optional embodiments, the expansion rate of the negative electrode sheet at 100% SOC state is 20%-30% compared to that at 0% SOC state.

[0028] According to an embodiment of the present application, in a third aspect, an electrical device is provided, comprising the secondary battery described in the second aspect of the present application.

[0029] The technical solution of this application has the following advantages:

[0030] The silicon negative electrode material provided by the present application includes silicon-based particles and fast ion conductors, the silicon-based particles have a porous structure, and the fast ion conductors are filled in the pores of the porous structure; the silicon-based particles include silicon elements and doping elements, and the doping elements include at least two of the IIIA group elements, the VIA group elements and the lanthanide series elements. The present application introduces at least two of the IIIA group elements, the VIA group elements and the lanthanide series elements into the silicon-based particles, and utilizes the different functions of different doping elements. Through the above design, the transmission rate of lithium ions / electrons inside the negative electrode sheet can be improved, and the volume expansion of the silicon negative electrode can be alleviated; at the same time, the silicon-based particles also have a porous structure, and the pores of the porous structure are filled with fast ion conductors, thereby not only further improving the conduction rate of lithium ions in the negative electrode, but also further alleviating the volume expansion, so as to ensure the good rate and cycle performance of the secondary battery.

[0031] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0033] Figure 1 It is a schematic diagram of the structure of the silicon negative electrode material prepared in this application.

[0034] The reference numerals are described as follows:

[0035] 1. Silicon-based particles; 2. Fast ion conductor. DETAILED DESCRIPTION

[0036] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0037] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0038] In order to solve the problem of poor rate and cycle performance of existing sulfide-type all-solid-state batteries, according to the first aspect of the present application, a silicon negative electrode material is provided, see Figure 1 , the silicon negative electrode material comprises silicon-based particles 1 and fast ion conductors 2, the silicon-based particles 1 have a porous structure, and the fast ion conductors 2 are filled in the pores of the porous structure;

[0039] The silicon-based particles 1 include silicon and doping elements, wherein the doping elements include at least two of group IIIA elements, group VIA elements, and lanthanide elements.

[0040] The silicon negative electrode material provided in the present application introduces at least two of the Group IIIA elements, Group VIA elements and lanthanide elements into silicon-based particles, and utilizes the different functions of different doping elements. Through the above design, the transmission rate of lithium ions / electrons inside the negative electrode sheet can be improved, and the volume expansion of the silicon negative electrode can be alleviated; at the same time, the silicon-based particles also have a porous structure, and the pores of the porous structure are filled with fast ion conductors, thereby not only further improving the conduction rate of lithium ions in the negative electrode, but also further alleviating the volume expansion, so as to ensure good rate and cycle performance of the secondary battery.

[0041] Specifically, the introduction of Group IIIA elements can play a skeleton role, especially when Group IIIA elements include at least one of B and In, they can form corresponding silicon alloys with silicon, so that the skeleton structure is not easy to collapse, so it can mainly improve the structural stability of the silicon negative electrode. In addition, the silicon alloy formed also has a slight effect on improving the transmission rate of lithium ions / electrons in the silicon negative electrode. The introduction of Group VIA elements can improve the electronic conductivity by adjusting the band structure of the material, and on the other hand, it can reduce the brittleness of the silicon negative electrode and delay the particle breakage when the particle changes in volume. In addition, Group VIA elements include at least one of S and Se, which can form chemical bonds with silicon, enhance the connection ability between atoms, and improve the structural stability of the silicon negative electrode during the process of lithium insertion and extraction. The introduction of lanthanide elements can increase the transmission rate of lithium ions, especially when the lanthanide elements include at least one of La and Ce, which can accelerate the transmission of lithium ions by widening the size of the channel for lithium ion transmission.

[0042] It is understandable that the content of doping elements in silicon-based particles has a great influence on the improvement of material properties. In some embodiments, the molar ratio of the IIIA group element in the silicon negative electrode material is 0.1-0.2, for example, it can be 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, etc. or within the range of any of the above values. The molar ratio of the VIA group element in the silicon negative electrode material is 0.1-0.2, for example, it can be 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, etc. or within the range of any of the above values. The molar ratio of the lanthanide in the silicon negative electrode material is 0.05-0.1, for example, it can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, etc. or within the range of any of the above values. This can increase the transmission rate of lithium ions / electrons in the silicon negative electrode, improve the structural stability of the silicon negative electrode, and slow down the volume change of the silicon negative electrode.

[0043] It should be noted that the silicon-based particles described in the present application are prepared by adding silicon and doping elements to a high-energy ball mill (the advantage of a high-energy ball mill over a conventional ball mill is that it can provide a higher capacity during the grinding process, promoting the uniform entry of doping atoms into the bulk structure of the silicon negative electrode), grinding at a speed of 500-1000 rpm for 20-30 hours to obtain silicon-based particles containing doping elements, and then etching with acid to obtain silicon-based particles with a porous structure. The liquid phase impregnation method is then used to load the fast ion conductor into the pores of the silicon-based particles with a porous structure, thereby obtaining the silicon negative electrode material described in the present application.

[0044] The porosity of the silicon negative electrode material provided in the present application is in the range of 1%-15%, which can effectively alleviate the volume expansion of the silicon negative electrode, and also facilitate the filling of the fast ion conductor in the pores of the silicon negative electrode material, thereby improving the transmission rate of lithium ions. As an example, the porosity of the silicon negative electrode material can be, for example, 1%, 3%, 5%, 7%, 10%, 13%, 15%, etc., or within the range of any of the above values.

[0045] In some embodiments, the median particle size of the silicon negative electrode material provided in the present application is 0.8μm-5μm. This can ensure a good bonding effect of the material on the current collector and improve the cycle stability of the silicon negative electrode. As an example, the median particle size of the silicon negative electrode material can be, for example, 0.8μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm, etc. or within the range of any of the above values. The median particle size in this application is the Dn50 of the material particles, which means the particle size corresponding to the number distribution percentage of the silicon negative electrode material reaching 50%.

[0046] It should be noted that the fast ion conductor described in the present application has good elasticity, and its elastic modulus is between 2MPa-200MPa, thereby more effectively alleviating the volume expansion of the silicon negative electrode while improving the lithium ion transmission rate. As an example, the elastic modulus of the fast ion conductor can be, for example, 2MPa, 10MPa, 25MPa, 50MPa, 75MPa, 100MPa, 125MPa, 150MPa, 175MPa, 200MPa, etc. or within the range of any of the above values.

[0047] In order not to affect the specific capacity of the silicon negative electrode and ensure a faster lithium ion transmission rate, in some embodiments, the content of the fast ion conductor is 5%-10% based on the mass of the silicon negative electrode material. As an example, the content of the fast ion conductor can be 5%, 6%, 7%, 8%, 9%, 10%, etc. or within the range of any of the above values.

[0048] In some embodiments, the fast ion conductor includes at least one of a sulfide electrolyte, a polymer electrolyte, and an oxygen-containing inorganic electrolyte. As an example, the sulfide electrolyte includes Li 10 GeP2S 12 、Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5, Li3PS4; the polymer electrolyte includes at least one of polyethylene oxide (PEO), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polymethyl methacrylate (PMMA), and polyacrylonitrile (PAN); the oxygen-containing inorganic electrolyte includes Li7La3Zr2O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1.3 Al 0.3 Ge 1.7 (PO4)3、Li 0.33 La 0.55 At least one of TiO3. The above fast ion conductor has excellent ion conductivity, which is beneficial to improving the transmission rate of lithium ions.

[0049] In some implementations, the fast ion conductor is a mixture of a polymer electrolyte and an oxygen-containing inorganic electrolyte, and the content of the oxygen-containing inorganic electrolyte is 10%-20% based on the mass of the fast ion conductor, which can further accelerate the transmission of lithium ions.

[0050] According to the second aspect of the present application, a secondary battery is provided, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte, wherein the negative electrode sheet comprises a negative electrode collector and a negative electrode active layer arranged on at least one side surface of the negative electrode collector, and the negative electrode active layer comprises the silicon negative electrode material described in the first aspect of the present application.

[0051] In some embodiments, the sheet resistance of the negative electrode sheet is 0.5 mΩ-1 mΩ, thereby ensuring good rate performance of the battery. As an example, the sheet resistance of the negative electrode sheet can be 0.5 mΩ, 0.6 mΩ, 0.7 mΩ, 0.8 mΩ, 0.9 mΩ, 1 mΩ, etc. or within the range of any of the above values.

[0052] In some embodiments, the expansion rate of the negative electrode sheet at 100% SOC is 20%-30% compared to that at 0% SOC, thereby ensuring a higher cycle performance of the battery. As an example, the expansion rate of the negative electrode sheet can be, for example, 20%, 22%, 24%, 26%, 28%, 30%, etc. or within the range of any of the above values. This shows that the use of the silicon negative electrode material of the present application can reduce the expansion rate of the electrode sheet, which is beneficial to the improvement of the cycle performance of the battery.

[0053] It is understood that the solid electrolyte described in the present application may be a sulfide-type solid electrolyte, and as an example may be Li 10 GeP2S 12 、Li7P3S 11 、Li6PS5Cl、Li 5.5PS 4.5 Cl 1.5 , Li3PS4 or at least one of the following.

[0054] According to an embodiment of the present application, in a third aspect, an electrical device is provided, comprising the secondary battery described in the second aspect of the present application.

[0055] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0056] Example 1

[0057] This embodiment provides a method for preparing a secondary battery, comprising the following steps:

[0058] (1) Preparation of silicon negative electrode materials

[0059] Si powder (Dn50 is 3μm) and B, S, and La elemental powders are ground in a high-energy ball mill at a molar ratio of 0.75:0.1:0.1:0.05 at a speed of 500rpm for 10 hours to obtain silicon-based particles doped with B, S, and La elements; the silicon-based particles are etched with 0.1M hydrofluoric acid to form silicon-based particles with a porous structure with a porosity of 25%.

[0060] PVDF-HFP was dissolved in DMF solvent (N,N-dimethylformamide) and Li7La3Zr2O was added 12 (LLZO), the mass ratio of PVDF-HFP and LLZO is 85:15, and a fast ion conductor solution with a concentration of 0.5M is prepared; the silicon-based particles with a porous structure are immersed in the fast ion conductor solution, stirred for 12 hours, and then filtered and dried to obtain a silicon negative electrode material, and the porosity of the silicon-based negative electrode material is 10%.

[0061] (2) Preparation of negative electrode sheet

[0062] The silicon negative electrode material, conductive agent carbon nanotube (CNT), and binder polyacrylic acid (PAA) prepared in step (1) are mixed uniformly in a weight ratio of 90:5:5, and distilled water is added, and the ratio of the mass of distilled water to the total mass of the above three substances is 80:20. After stirring for 1 hour using a planetary stirring degassing machine, a negative electrode slurry is obtained. The negative electrode slurry is coated on the surface of the copper foil current collector and dried at 60°C.

[0063] (3) Assembly of all-solid-state batteries

[0064] Add Li6PS5Cl powder to the mold battery, and then apply 30MPa pressure for pre-pressing to obtain a solid electrolyte. Then place the negative electrode sheet prepared in step (2) on one side of the electrolyte, add indium sheet and lithium sheet on the other side, and apply 400MPa pressure to complete the assembly of the all-solid-state battery.

[0065] The preparation methods of Examples 2-17 and Comparative Examples 1-4 are substantially the same as those of Example 1, and the differences are shown in Table 1.

[0066] Table 1

[0067]

[0068]

[0069] Experimental example

[0070] 1. Elastic modulus test

[0071] The fast ion conductor slurry was scraped onto the PET base film, and after drying, a fast ion conductor film was obtained. Then, the Young's modulus of the fast ion conductor was tested using an atomic force microscope (AFM).

[0072] 2. Median particle size test

[0073] The prepared silicon-based negative electrode powder was tested for particle size distribution using a laser particle size analyzer to obtain the median particle size.

[0074] 3. Porosity test

[0075] The prepared silicon-based negative electrode powder was tested for adsorption-desorption curve using the gas adsorption method (BET method), and the porosity of the material was further calculated.

[0076] 4. Diaphragm resistance test

[0077] The prepared silicon-based negative electrode sheet was tested for membrane resistance using the four-probe method.

[0078] 5. Expansion rate test

[0079] The length, width and height of the initial electrode are tested to obtain the initial volume V1 of the electrode (under 0% SOC state), and then the electrode is assembled into a battery for electrochemical lithium insertion. The battery is disassembled in the fully inserted state, and the length, width and height of the electrode are tested again to obtain the volume V2 after full insertion. The expansion rate = (V2-V1) / V1*100%.

[0080] 6. Battery performance test

[0081] The cycle performance of the all-solid-state battery was measured using a 9th-generation Xinwei machine with a cut-off voltage of 2.5-4.3V. It was first cycled at 0.1C for 3 cycles and then cycled at 1C for 500 cycles.

[0082] 1C capacity retention rate = 100% * first cycle discharge capacity under 1C conditions / first cycle discharge capacity under 0.1C conditions;

[0083] 500-cycle capacity retention rate = 100% under 1C condition * discharge capacity after 500 cycles / discharge capacity of the first cycle.

[0084] Please see Table 1-Table 2 for the above test results.

[0085] Table 2

[0086]

[0087] From Table 1 and Table 2, it can be seen that introducing at least two of the Group IIIA elements, Group VIA elements, and lanthanide elements into the porous silicon negative electrode material and providing a fast ion conductor in the pores can inhibit the collision of the pole pieces and significantly improve the rate performance and cycle stability of the battery.

[0088] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.

Claims

1. A silicon negative electrode material, characterized in that: The silicon negative electrode material comprises silicon-based particles and fast ion conductors, wherein the silicon-based particles have a porous structure, and the fast ion conductors are filled in the pores of the porous structure; The silicon-based particles include silicon element and a doping element, wherein the doping element includes at least two of Group IIIA elements, Group VIA elements, and lanthanide elements.

2. The silicon negative electrode material according to claim 1, characterized in that: Includes at least one of the following features: a. The Group IIIA element includes at least one of B and In; b. The VIA group element includes at least one of S and Se; c. The lanthanide element includes at least one of La and Ce.

3. The silicon negative electrode material according to claim 1 or 2, characterized in that: Includes at least one of the following features: d. The molar ratio of the Group IIIA element in the silicon negative electrode material is 0.1-0.2; e. The molar ratio of the VIA group element in the silicon negative electrode material is 0.1-0.2; f. The molar ratio of the lanthanide element in the silicon negative electrode material is 0.05-0.

1.

4. The silicon negative electrode material according to claim 1, characterized in that: The porosity of the silicon negative electrode material is 1%-15%; And / or, the median particle size of the silicon negative electrode material is 0.8 μm-5 μm.

5. The silicon negative electrode material according to claim 1, characterized in that: Includes at least one of the following features: g. Based on the mass of the silicon negative electrode material, the content of the fast ion conductor is 5%-10%; h. The elastic modulus of the fast ion conductor is 2MPa-200MPa; i. The fast ion conductor comprises at least one of a sulfide electrolyte, a polymer electrolyte, and an oxygen-containing inorganic electrolyte.

6. The silicon negative electrode material according to claim 5, characterized in that: The fast ion conductor is a polymer electrolyte and an oxygen-containing inorganic electrolyte. Based on the mass of the fast ion conductor, the content of the oxygen-containing inorganic electrolyte is 10%-20%.

7. The silicon negative electrode material according to claim 5 or 6, characterized in that: The sulfide electrolyte includes Li 10 GeP2S 12 、Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 , at least one of Li3PS4; The polymer electrolyte comprises at least one of polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, and polyacrylonitrile; The oxygen-containing inorganic electrolyte includes Li7La3Zr2O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1.3 Al 0.3 Ge 1.7 (PO4)3、Li 0.33 La 0.55 At least one of TiO3.

8. A secondary battery comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer arranged on at least one side surface of the negative electrode current collector, and the negative electrode active layer comprises the silicon negative electrode material according to any one of claims 1 to 7.

9. The secondary battery according to claim 8, characterized in that: The film resistance of the negative electrode sheet is 0.5mΩ-1mΩ; And / or, the expansion rate of the negative electrode sheet at 100% SOC state is 20%-30% compared with that at 0% SOC state.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Cerium-boron co-doped silicon-based composite material as well as preparation method and application thereof

    CN116111055A

  • Long cycle life, high capacity silicon anodes and methods of making and using same

    CN116964802A

  • Silicon negative electrode material and preparation method and application thereof

    CN117673280A

  • Negative electrode active material and battery

    CN118020169A

  • Sulfur-doped silicon negative electrode material, method for producing same, lithium secondary battery negative electrode including negative electrode material, and lithium secondary battery comprising negative electrode

    US20210328214A1

Cited By

  • Porous silicon negative electrode, preparation method thereof and solid-state battery

    CN121123180A